Ionic liquid tailored interfaces in halloysite nanotube/heterophasic ethylene–propylene copolymer nanocomposites with enhanced mechanical properties. (September 2016) - Bischoff, E.; Simon, D.A.; Schrekker, H.S.; Lavorgna, M.; Ambrosio, L.; Liberman, S.A.; Mauler, R.S.
Graphical abstract: Highlights: Modification of HNT with ionic liquid strongly affects interaction with polymer. Ionic liquid coated particles increase polymer toughness while maintain stiffness. Ionic liquid chemical structure affect polypropylene crystallization. Abstract: In this study, imidazolium ionic liquids (IL) were investigated as novel compatibilizers to improve the dispersion of halloysite nanotubes (HNT) in heterophasic ethylene-propylene copolymer (EPP) matrix to enhance the mechanical properties of the EPP/HNT nanocomposites prepared by melt-blending approach. The results highlight that the dispersion of HNT nanotubes and consequently the mechanical properties of nanocomposites depends on the surface modification of HNT with IL, which in turn strongly depends on the chemical structure of IL, i.e. anion and cation N-alkyl chain length, as well as on the adsorption conditions, e.g. solvent polarity and IL concentration adopted for the modification of HNT surface. In details the nanocomposites with HNT modified by IL (m-HNT ) exhibited a more homogeneous HNT dispersion above all when the IL surface modification was conducted in less polar solvents as dichloromethane. Furthermore, the IL allowed to tuning the stiffness and the toughness with a right compromise. The EPP/m-HNT nanocomposites with bis(trifluoromethylsulfonyl)imide [NTf2 ] anion and 1-methyl-3- n -octadecylimidazolium cation-based IL, exhibited an improvement of elastic modulus of about 34% with respect to the pristine polymer, without loss of the impact properties at 23 °C. The morphological and mechanical results confirm the IL acted effectively as compatibilizer, improving both the interfacial interaction and HNT dispersion into the EPP matrix.